2012
DOI: 10.1111/j.1469-185x.2012.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecophylogenetics: advances and perspectives

Abstract: Ecophylogenetics can be viewed as an emerging fusion of ecology, biogeography and macroevolution. This new and fastgrowing field is promoting the incorporation of evolution and historical contingencies into the ecological research agenda through the widespread use of phylogenetic data. Including phylogeny into ecological thinking represents an opportunity for biologists from different fields to collaborate and has provided promising avenues of research in both theoretical and empirical ecology, towards a bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
437
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 371 publications
(454 citation statements)
references
References 159 publications
5
437
0
3
Order By: Relevance
“…While some ecoregions rank high regardless of which metric of ED is used, highlighting their importance from a conservation perspective, risk assessment of ecoregions that score high on one metric but not on the other is more difficult and involves qualitative decisions about which aspect of the diversification process we value more [101]. On one hand, if the goal is to preserve evolutionary heritage, a key component of biodiversity [5,7,10,102], then focusing our efforts on reef ecoregions with high-standing PD (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While some ecoregions rank high regardless of which metric of ED is used, highlighting their importance from a conservation perspective, risk assessment of ecoregions that score high on one metric but not on the other is more difficult and involves qualitative decisions about which aspect of the diversification process we value more [101]. On one hand, if the goal is to preserve evolutionary heritage, a key component of biodiversity [5,7,10,102], then focusing our efforts on reef ecoregions with high-standing PD (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although ecological studies have traditionally looked at how species assemble into communities and impact EF, evolutionary studies have con centrated on the diversification processes responsible for the range of functional traits we observe in nature 4,5 . The emerging fields of evolutionary community ecology and ecophylogenetics integrate these distinct perspectives of biodiversity to provide tools for its conservation and the provision of ecosystem services [4][5][6][7][8][9] .…”
mentioning
confidence: 99%
“…It is hypothesized that if closely related species are ecologically similar (that is, trait conservatism), EF such as productivity should increase with PD 14 . As we usually have imper fect knowledge of the distribution of functional traits responsible for resource acquisition and species interactions, the knowledge of the evolutionary relationships could thus be used as a proxy for func tional diversity 4,9,14 . Accordingly, comparative analyses have shown that phylogenetic relatedness was a reasonable proxy of functional trait diversity and therefore a good predictor of EF [14][15][16] .…”
mentioning
confidence: 99%
“…The use of alpha-level phylogenetic diversity is based on the assumption that it would correlate with ecological processes better than species richness of the community (Forest et al 2007), and therefore work as an indicator for functional diversity when species traits data are missing. This is based on the idea that phylogenetically distinct species are likely to be functionally different (Cadotte et al 2008), although this assumption has also been challenged (Mouquet et al 2012). For this purpose, phylogenetic diversity indices that account for species abundances (Chao et al 2010;Chao et al chapter "Phylogenetic Diversity Measures and Their Decomposition: A Framework Based on Hill Numbers") might be more suitable than the ones that consider only presences and absences of species (such as Faith 1992): from the perspective of ecosystem function, viable populations and sparse individuals of a species should not be considered equally important.…”
Section: Boxmentioning
confidence: 99%